Knowledge Level of Pregnant Women about 3M Affects 3M Implementation Compliance During the Pandemic - Nur Afifah; Yuni Puji Widiastuti; Qurrotul Aeni; Ahmad Asyrofi; Rina Anggraeni (Global Health Science Group, 2021)
Covid-19 can attack all walks of life, including pregnant women. Pregnant women are one of the vulnerable groups at risk of being infected with COVID-19 because during pregnancy physiological changes occur which result in a partial decrease in immunity and can cause serious impacts for pregnant women. Lack of knowledge will have an impact on non-compliance of pregnant women in implementing health protocols so that they are vulnerable to contracting Covid-19. The purpose of the study was to determine the effect of the level of knowledge of pregnant women about 3M on adherence to the application of 3M during the pandemic. Design The design of this study was a descriptive correlational study with a cross sectional approach. The sample in this study amounted to 66 respondents with purposive sampling technique. The study used a knowledge level questionnaire and 3M implementation compliance. Analysis of the data using the analysis of Descriptive Statistics and Chi Square. The results of this study indicate that the average age of the respondents is 29 years, the average is the 2nd pregnancy, the education level of the majority of respondents is high school education as many as 43 respondents (65.2%) and the level of knowledge of pregnant women about 3M in the good category is as much as 48 respondents (72.7%) and compliance with 3M implementation in the obedient category were 59 respondents (89.4%). Conclusion There is a significant relationship between the level of knowledge of pregnant women about 3M with adherence to the application of 3M during the pandemic (p = 0.01).